PEMBERIAN ASI EKSKLUSIF BERHUBUNGAN DENGAN RISIKO TERJADINYA TUBERKULOSA PARU PADA ANAK - Saman, Fransiska; Nursanti, Ida; Sumiyar Rini, Retno (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Indonesia is in the third rank in the quantity of tuberculosis patients. Based on data of World Health Organization in 2009 Indonesian rank declined to the fifth with as many as 429,000 people.Proportion of child TB patients among all TB cases in 2011 per province in 2011 was in the range of 1.7%-17.2%. Exclusive breastfeeding supplementation in infants of 0-1 year has a very important role,particularly in aspect of nutrition fulfillment and immunity against diseases. In the breast milk there factors of immunity such as lisozim and immunoglobulin A (Ig A) that can break the cell walls of enterobacter bacteria and positive gram bacteria on of which is Mycobacterium tuberculosis. Objective: To identify correlation between exclusive brestfeeding supplementation and the incidence of lung TB in children of 3-11 years at Jetis Health Center Yogyakarta. Methods: The study was an analytic survey with cross sectional design. Samples were purposively selected comprising 119 mothers and children of 3-11 years at Jetis Health Center Yogyakarta.  Research instruments were data of medical records and questionnaire. Analysis used chi square test. Result: The majority of mothers at Jetis Health Center Yogyakarta gave exclusive breastfeeding (87.4%). Most of the children of 3-11 years at Jetis Health Center Yogyakarta did not suffer from lung TB (70.6%). The result of chi square test showed p value (0.005) < 0.05 and contingency coefficient was 0.247. Conclusion: There was correlation between exclusive breastfeeding supplementation and the incidence of lung TB in children of 3-11 years at Jetis Health center Yogyakarta with low level of correlation. Keywords: Exclusive breastfeeding, lung tuberculosis, children under five years